The α-Terpineol to 1, 8-Cineole Cyclization Reaction of Tobacco Terpene Synthases. Issue 4 (11th October 2016) - Piechulla, Birgit; Bartelt, Richard; Brosemann, Anne; Effmert, Uta; Bouwmeester, Harro; Hippauf, Frank; Brandt, Wolfgang
Abstract : The conversion of α-terpineol to 1, 8-cineole by monoterpene synthases is initiated by a catalytic dyad, followed by a reaction via (S)-(−)-α-terpineol, and influenced by amino acids more than 10 Å away from the active site. Abstract: Flowers of Nicotiana species emit a characteristic blend including the cineole cassette monoterpenes. This set of terpenes is synthesized by multiproduct enzymes, with either 1, 8-cineole or α-terpineol contributing most to the volatile spectrum, thus referring to cineole or terpineol synthase, respectively. To understand the molecular and structural requirements of the enzymes that favor the biochemical formation of α-terpineol and 1, 8-cineole, site-directed mutagenesis, in silico modeling, and semiempiric calculations were performed. Our results indicate the formation of α-terpineol by a nucleophilic attack of water. During this attack, the α-terpinyl cation is stabilized by π-stacking with a tryptophan side chain (tryptophan-253). The hypothesized catalytic mechanism of α-terpineol-to-1, 8-cineole conversion is initiated by a catalytic dyad (histidine-502 and glutamate-249), acting as a base, and a threonine (threonine-278) providing the subsequent rearrangement from terpineol to cineol by catalyzing the autoprotonation of ( S )-(−)-α-terpineol, which is the favored enantiomer product of the recombinant enzymes. Furthermore, by site-directed mutagenesis, we were able to identify amino acids at positions 147, 148, and 266 that determine the different terpineol-cineole ratios in Nicotiana   suaveolens cineole synthase and Nicotiana   langsdorffii terpineol synthase. Since amino acid 266 is more than 10 Å away from the active site, an indirect effect of this amino acid exchange on the catalysis is discussed.